2018
DOI: 10.1002/slct.201702270
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Vesicular Self‐Assemblies of the Salts of a Natural Triterpenoid Arjunolic Acid into Superstructured Ambidextrous Gels and Study of Their Entrapment Properties

Abstract: Generation of supramolecular hydrogel from biocompatible supramolecular building blocks has become an area of tremendous research investigation because of it's potential use in biomedical sciences, food industries, cosmetics, etc. In recent years, the biocompatible nano‐sized trieterpenoid molecules have gained significant attention of the scientific community as supramolecular building blocks because of its unique molecular structures. Herein, we report the hierarchical self‐assembly properties of sodium and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Tremendous biological effects such as heart tonic [ 32 – 35 ], diuretic [ 36 ], cytotoxic [ 37 ], antibacterial, anti-platelet aggregation [ 38 – 42 ], anti-inflammatory, hepatoprotective [ 43 – 46 ], antitumor, anti hyperlipidemic, anti-ulcer, anti-depressant action in central nervous system [ 47 53 ] have been reported. During our investigations on the utilization of triterpenoids (C30 s) as renewable functional nano entities [ 54 58 ] it occurred to us that the medicinally important bark extract of Nerium oleander , rich in polyphenolic compounds, can be utilized for the synthesis AuNPs from HAuCl 4 . In this paper we report the green synthesis of gold-conjugated nanoparticles by the reaction of aqueous chloroauric acid with an ethanol extract of the stem bark of the Nerium oleander under very mild reaction conditions without any additional stabilizing or capping agents.…”
Section: Introductionmentioning
confidence: 99%
“…Tremendous biological effects such as heart tonic [ 32 – 35 ], diuretic [ 36 ], cytotoxic [ 37 ], antibacterial, anti-platelet aggregation [ 38 – 42 ], anti-inflammatory, hepatoprotective [ 43 – 46 ], antitumor, anti hyperlipidemic, anti-ulcer, anti-depressant action in central nervous system [ 47 53 ] have been reported. During our investigations on the utilization of triterpenoids (C30 s) as renewable functional nano entities [ 54 58 ] it occurred to us that the medicinally important bark extract of Nerium oleander , rich in polyphenolic compounds, can be utilized for the synthesis AuNPs from HAuCl 4 . In this paper we report the green synthesis of gold-conjugated nanoparticles by the reaction of aqueous chloroauric acid with an ethanol extract of the stem bark of the Nerium oleander under very mild reaction conditions without any additional stabilizing or capping agents.…”
Section: Introductionmentioning
confidence: 99%
“…Gelation ability of salts obtained from triterpenoids was also investigated. A simple [ OA ]-[choline] salt (structure is not shown) was prepared and studied as a hydrogelator to form a novel LMWG . The authors found that the [ OA ]-[choline] salt showed unique characteristics in contrast to the common sol ⇔ gel transitions.…”
Section: An Approach To the Pentacyclic Triterpene Scaffolds As Poten...mentioning
confidence: 99%